The Effect of Emotional Intelligence on Employees’ Job Performance in the Ethiopian Public Sectors - Solomon, Bereket Solomon (African Journal of Leadership and Development, 2024)
Emotional Intelligence (EI) has been claimed important for performance of leaders and workers in organizations. But little research has examined these issues in the Ethiopian context in general and in the public sector in particular. Hence, this study explores the relationship between the four dimensions of Emotional Intelligence: self-awareness, self-management, social awareness and social skills. Hence, in order to address this research objective, the study employed a mixed research approach with descriptive and explanatory research designs. A total of 308 usable questionnaires were used for further analysis. The descriptive statistics results revealed that, the level of emotional intelligence is at average or moderate level in the public sector in terms of the four dimensions of emotional intelligence skills. The correlation result, confirmed that, all the four dimensions of emotional intelligence skills have a positive and strong to moderate relation with employees’ job performance. Furthermore, the regression analysis confirmed that, all the four dimensions of emotional intelligence skills have a positive and significant effect on employees’ job performance. The result was further supported with SEM analysis and it was verified that, self-emotional appraisal and others’ emotional appraisal have the strongest effect on employees’ job performance. Based on the results of the study, it is recommended that, the organizations need to focus on conducting employee emotional intelligence skill test apart from the conventional aptitude tests during selection and recruitment process. recruiting employees externally or promoting employees internally, should not only be based on indicators such as their academic qualifications, but it is also equally important to consider and evaluate their emotional intelligence. Improving the sense of organizational support should also receive the organization's attention. The sense of organizational support will have a positive impact on the positive work behavior of employees.